Evaluación de la síntesis de biodiésel mediante el uso de residuos de Aguacate Hass (semilla) empleando el método de transesterificación (2020)
We worked with the oils extracted from the Hass avocado (Persea americana var Hass), using the residue as is the almond. For this, the respective extraction processes were carried out by mechanical pressing, refining, and transesterification of the oils. The transesterification reaction was carried out in a homogeneous and alkaline environment. The biofuel obtained at the end of the process was contrasted with the requirements of the standards for diesel biofuels (ASTM D6751). This allowed evaluating different operating conditions and thus the one with the best performance was chosen to carry out a pilot plant scale process design, and an economic study to determine the costs of biodiesel production.